2006
DOI: 10.1538/expanim.55.477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methamphetamine on Cortisone Concentration, NK Cell Activity and Mitogen Response of T-lymphocytes in Female Cynomolgus Monkeys

Abstract: As a model for studying methamphetamine (MAP) abuse, which has become a social problem in Japan, we investigated the changes in serum cortisone, NK cell activity and mitogenic response of T-lymphocytes after a single injection of MAP (3.0 mg/kg) levels. In Japan, MAP has been illegally used as a stimulant in recent years to relieve fatigue, and its abuse has spread among the general public, young people and even housewives. There are reports of deaths in humans [4,8], and animal experiments have investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Moreover, in MA-ER mice, plasma levels of IL-6 were decreased, and IL-10 levels were increased compared with SAL-ER mice. These latter data are generally consistent with the suppressive effects of MA on peripheral immune function (Martinez et al 2009; Saito et al 2006; In et al 2005; Yu et al 2002) as well as the inhibitory effects of MA on transcription factors critical for the expression of proinflammatory cytokines (Ye et al 2008), but since these effects were only significant in the ER group, this suggests that the immunosuppressive effects of MA may be most pronounced during active use or early in remission. The question of how MA-induced peripheral immune dysregulation relates to persistent alterations in brain neuroanatomy and function is complex and one that requires a translational research approach to comprehensively address.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, in MA-ER mice, plasma levels of IL-6 were decreased, and IL-10 levels were increased compared with SAL-ER mice. These latter data are generally consistent with the suppressive effects of MA on peripheral immune function (Martinez et al 2009; Saito et al 2006; In et al 2005; Yu et al 2002) as well as the inhibitory effects of MA on transcription factors critical for the expression of proinflammatory cytokines (Ye et al 2008), but since these effects were only significant in the ER group, this suggests that the immunosuppressive effects of MA may be most pronounced during active use or early in remission. The question of how MA-induced peripheral immune dysregulation relates to persistent alterations in brain neuroanatomy and function is complex and one that requires a translational research approach to comprehensively address.…”
Section: Discussionsupporting
confidence: 73%
“…Studies have found that morphine suppressed T cell activation in the lymph node, paralleled with a decrease in activation levels of T cells in peripheral blood in nonhuman primates [126]. Methamphetamine has been shown to accelerate the premature demise of activated T cells [127], and reduce the number of dendritic cells and natural killer cells [128,129]. Other than that, excessive reactive oxygen species is produced when astrocytic cells are treated with methamphetamine via CYP2E1, leading to apoptotic cell death [95].…”
Section: Autophagy In Hiv-1 With Co-exposure Of Doamentioning
confidence: 99%
“…We previously reported an increase in serum cortisone, a transient increase in NK cell activity followed by a distinct drop, and elevation in the mitogenic response (PHA) of lymphocytes after a single injection of MAP in female cynomolgus monkeys. From those findings, we assumed that the effects of MAP on the immune system are strongly related to the cortisone concentration [24]. Scheiman et al [25] suggested that nuclear factor kappa B, a regulator of the immune system, might be a target for glucocorticoid-mediated immunosuppression.…”
Section: Introductionmentioning
confidence: 96%